Pengaruh Penerapan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Sub Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Murniati, Hafizh Naufal Nawawi, (GLOBAL SCIENTS PUBLISHER, 2024)
This study aims to prove and analyze the effect of the implementation of Good Corporate Governance on the financial performance of banking sub-sector companies listed on the Indonesia Stock Exchange, data used from 2019 to 2023. This study used 34 banking sub-sector companies on the Indonesia Stock Exchange. Sampling was carried out using the purposive sampling method. The dependent variable in this study is financial performance and the independent variables are the Board of Commissioners, Board of Directors, Audit Committee and Public Ownership. The results of the study show that the Audit Committee and Public Ownership have a positive and significant effect on Financial Performance. While the Board of Directors has a negative and significant effect on Financial Performance and the Board of Commissioners does not have a significant effect on the Financial Performance of banking sub-sector companies on the Indonesia Stock Exchange in 2019-2023.